Broadband inductorless vector modulator IC for localisation and communication systems. Issue 10 (1st May 2015) - Wagner, J.; Joram, N.; Wolf, R.; Ellinger, F.
Abstract : An inductorless vector modulator‐based radio frequency (RF) weighting circuit working from 1 to 10 GHz is presented. Amplitude and phase interdependencies were strongly reduced employing optimised attenuators. The vector modulator features a 360° phase and more than 40 dB amplitude control range with a root mean square phase and amplitude error of only 6° and 0.16 dB, respectively. These features make it a suitable candidate for communication and localisation diversity frontends in the 2.4 and the 5.9 GHz industrial, scientific and medical (ISM) bands. The circuit was fabricated in a 180 nm BiCMOS technology and contains an inter‐integrated circuit (I 2 C) control interface and digital‐to‐analogue converters. It consumes 87 mW and requires an area of only ≃0.2 mm 2 .